Autonomous Mobile Mapping Robots - Bȩdkowski, Janusz (IntechOpen, 2023)
This book presents recent research advances in autonomous mobile mapping robots, covering a range of topics. These include unconventional trajectories for mobile 3D scanning, key software components such as lidar odometry, look closure, pose graph SLAM, map refinement, path planning, and coverage algorithms. The book also explores multi-robot mapping and scalable algorithms for simultaneous localization and mapping. Finally, it delves into real-world applications like aerial 3D mapping and automotive SLAM in urban environments.